Urinary incontinence in institutionalized elderly: prevalence and impact on quality of life - Javier Jerez Roig; Dyego Leandro Bezerra de Souza; Kenio Costa Lima
AbstractIntroduction Urinary incontinence is a geriatric syndrome that generates strong economic and social impacts as well as emotional changes and negative consequences for the health of the elderly.Objective The objective of this work was to identify the prevalence of urinary incontinence and its associated factors, as well as its impact on quality of life of institutionalized elderly.Materials and methods A cross-sectional study was conducted herein, with 10 long-term institutions for the elderly of the municipality of Natal (Northeast Brazil). The Minimum Data Set was completed by caregivers to determine the presence of incontinence, and the Short Form of the International Consultation on Incontinence Questionnaire was answered by the elderly, to assess the frequency and amount of urinary leakage, the impact on quality of life, and the type of incontinence. The chi-square test and Fisher's exact test were applied in the bivariate analysis, and logistic regression was utilized for multivariate analysis.Results The prevalence of urinary incontinence was 42.7% (95% CI: 34.8-50.8). The impact of this condition on daily life was mild in 46.5% of cases, moderate for 29.3% of cases, and severe in 24.1% of cases. The condition was associated with functional impairment (p < 0.001; RP: 4.13).Final considerations The prevalence of urinary incontinence in this sample, which presented cognitive ability to answer questionnaires, was over 40% with a high degree of severity. Approximately half of the incontinents referred a moderate-severe impact of incontinence. Control measures for this geriatric syndrome within the institutions are important to delay the decline of health and improve the quality of life of the residents.